Judges, technology and artificial intelligence : the artificial judge - Sourdin, Tania (Elgar law, technology and society series, 2021)
"New and emerging technologies are reshaping justice systems and transforming the role of judges. The impacts vary according to how structural reforms take place and how courts adapt case management processes, online dispute resolution systems and justice apps. Significant shifts are also occurring with the development of more sophisticated forms of artificial intelligence that can support judicial work or even replace judges. These developments, together with shifts towards online court processes are explored in Judges, Technology and Artificial Intelligence. By considering how different jurisdictions are approaching current and future technological shifts and in particular by focusing on the different approaches in the US, UK, Australia and China and elsewhere, the author draws rich comparative exploration of justice technology trends. Judicial commentary is considered as well as the growing scholarly discourse about these trends. Ethical and user centred design options are examined in the context of how responsive judges engage with supportive, replacement and disruptive technologies in courts. This book is relevant to current issues about the responsiveness of the justice system in the pandemic era, and how technology can respond and shift justice processes is a growing field of research, for judges, scholars, students and justice commentators. It provides a much-needed resource on an increasingly important topic"--